Formulation of life cycle sustainable assessment of palm oil production in Johor, Malaysia - Naseb, Najat O. M. (2020)
Palm oil is one of the most important vegetable oils in the world and each year a million tonnes of palm oil has been traded globally to be consumed by millions of people around the world. The palm oil industry has evolved dramatically and hence produced varieties of products such as crude palm oil, palm kernel oil, palm kernel cake, oleo-chemical as well as new bio-fuel products to fulfil the demand. However, the rapid development of this industry in developing countries has become a subject of increasing international and national concern. Although the Malaysian palm oil is the most important agricultural commodity in this country and contributes substantially to the economy, the Malaysian palm oil industry has faced some negative reports that may affect the industry’s future sustainability. This study aims to provide a comprehensive assessment on the impact of palm oil production on the basis of the three sustainability dimensions in order to assist in decision making for sustainable production. Therefore, this study developed a life cycle sustainability assessment (LCSA) methodology, which combined three life-cycle based methods, namely, life cycle assessment (LCA), life cycle costing (LCC) and social life cycle assessment (SLCA) using the scoring system method. Firstly, the three life-cycle-based methods were carried out to measure the impact on the product life cycle for a functional unit (FU) of 1 MT crude palm oil produced. Environmental impacts were assessed using the International Organization for Standardization (ISO) standardized LCA. Economic impacts were evaluated using life cycle costing. Social impacts were determined using a social life cycle assessment methodology. Two stakeholder categories were identified, including workers and the local community. Second, the three life-cycle based methods were integrated within the LCSA method using the scoring system method. Finally, a presentation technique was developed to visualize the LCSA results. The applicability and validity of this method were demonstrated using a case study. The case study evaluated the sustainability of crude palm oil at two selected based plantation mills in Johor. The proposed method facilitated the evaluation and interpretation of the results of the three dimensions and this provided a comprehensive assessment of crude palm oil production. The results obtained show that crude palm oil production require more improvement to be a sustainable product. However, this study attempted to achieve better communication and comprehension of LCSA results by developing a presentation technique to visualize the results obtained from the three methods. The findings of this study made it feasible for the decision-makers to understand the significant hotspots related to various environmental economic and social impacts in order to promote the sustainability of crude palm oil production.